Intimacy, Parkinson's disease and dementia in the time of the coronavirus - Gila Bronner; Amos D Korczyn; Tanya Gurevich (Archive of Gerontology and Geriatrics Research - Peertechz Publications, 2020)
While the corona virus does not seem to invade the brain, patients with neurodegenerative diseases do not suffer from specific deficits in their immune system which could put them at increased risk of SARS-CoV-2 infection. So far, experience from the affected regions does not show an apparent increased risk, although there are no systematic data yet available [1].